The Effectiveness Analysis of Bus Rapid Transit Services (A Case Trans Semarang, Indonesia) - Sony, Sony; Rifai, Andri Irfan; Handayani, Susanty (DAS Institute, 2022)
The population density in the city of Semarang, which is the impact of the flow of urbanization, is in line with the high demand for transportation. This situation also creates a new problem for the city: traffic jams. Traffic jam occurs because the available road capacity needs to be balanced with the number of vehicles used. In addition, the people of Semarang City tend to use private Transportation rather than public Transportation provided by the city government, namely Bus Rapid Transit (BRT). This research was conducted to analyze the effectiveness of Semarang BRT in meeting the high transportation needs in the city of Semarang. The research results will show aspects of BRT that need to be developed or improved, thereby increasing public interest in choosing to use the public transportation provided. Several indicators of Semarang BRT service quality have been assessed as good, with the highest tariff parameter. This condition illustrates that BRT tariff determination can still provide good service for road users. Meanwhile, the parameters that were considered bad service were disabled facilities and pregnant women.